Quality assessment model of environmental information disclosure - Karlonaitė, Inga; Rudžionienė, Kristina (Buhalterinės apskaitos teorija ir praktika, 2014)
In last decades, environmental issues: pollution, climate change, sing of non-renewable resources, has influenced the economic value of nature and the protection of the environment has become an important goal for institutions and corporations. Increasing concern to environmental problems causes increasing demand for environmental disclosure of environmental related information. Responding to the increasing demand for such type of information, interest of environmental accounting and reporting is growing too. It is especially needed for the disclosed information to be useful and in high quality.Purpose of this work –prepare and adjust quality assessment model of environmental information disclosure. Case study indicates that this model is suitable for Baltic countries companies. Companies mostly disclose information about environmental costs, waste, pollution, programs, projects or activities in social life and regulations they follow. Lithuanian companies are most improved in this area, because 93,75% of companies discloses that information in financial reports, separate reports or internet pages.
Keywords: environmental accounting; quality of environmental information disclosure; model